Breach of Non-Competition Clause in Franchise Agreements Related to Unfair Business Competition - Indrawati, Etty; Widiyastuti, Y. Sari Murti (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
The non-competition clause in the franchise agreement is the franchisee's commitment not to run a similar business or potentially become a competitor to the franchisor's business within a certain period as a form of protection of the franchisor's intellectual property rights and appreciation for the transfer of know-how that the franchisor has carried out in the form of knowledge, concept, and experience to the franchisee. There are two purposes of this article. First is to explore and analyze cases of breach of the non-competition clause in franchise agreements in Indonesia carried out by franchisees can be qualified or not as a form of unfair business competition as regulated in Article 1 number 6 Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. Second is to investigate the legal remedies taken by the franchisor against the franchisee who breaks the non-competition clause in the franchise agreement. This research project uses qualitative method. This research involved respondents and informants from business owners of national franchisors. There are two results of this study. First, breaking non-competition clauses in franchise agreements, which have been read before signing, can qualify as unfair business competition. Second, if a franchisee or former franchisee breaks a non-competition clause, it is necessary to communicate with the violating party first before giving a summons/warning. Moreover, if it is still not heeded, the franchisor can file a lawsuit in court or submit a complaint to The Indonesia Competition Commission (KPPU).